The Location (And Founding) of a Town of Poznań in Light of the Earliest Documents and Narrative Sources - Dobosz, Józef (Studia Historiae Oeconomicae, 2013)
The paper addresses the issue of the origins of the town of Poznań founded in mid-13th century under German law. The birth of the charter town on the left bank of the Warta river is illustrated first and foremost by sources: documents from the mid-13th century, particularly a location charter of 1253, and narrative sources, e.g. The Wielkopolska Chronicle and yearly records written in Wielkopolska. The town was the work of Przemysł I, the duke of Wielkopolska, who sorted out property issues on the left bank of the Warta, made grants and granted privileges, erected his new castle next to the new town, and together with his brother Bolesław issued a location charter in 1253. The duke’s action resulted in the rise of one of the most important urban centers in medieval Poland.